Biomarkers indicating tissue thyroid hormone status: ready to be implemented yet?. Issue 2 (31st March 2022) - Jansen, Heleen I; Bruinstroop, Eveline; Heijboer, Annemieke C; Boelen, Anita
Abstract : Currently, thyroid hormone status is predominantly determined by the measurement of serum thyroid-stimulating hormone and free thyroxine. Although it is assumed that serum thyroid hormone (TH) concentrations within the reference range represent euthyroidism, it is unknown whether this reflects euthyroidism in all tissues (e.g. brain, muscle, bone and liver). To date, no serum marker has been established for clinical use that represents TH status within tissues accurately. However, several biomarkers have been investigated and innovative techniques have been used to unravel new biomarkers. This review provides an overview of proposed serum biomarkers that reflect tissue TH status in humans. Furthermore, we discuss the feasibility of these serum markers in clinical practice.